The role of interleukin-10 and its encoding gene polymorphism influence on the course of infections caused by varicella-zoster virus - N. V. Onishchenko; Yu. Yu. Riabokon; A. V. Abramov (Zaporožskij Medicinskij Žurnal)
The purpose is to find out the role of changes in the quantitative content of IL-10 in association with the polymorphism of gene encoding it (rs 1800872) in the course of chickenpox and herpes zoster.